(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article highlights modern methods for the formation of knowledge, skills and abilities of students in the process of medical education in the context of digital education and digital pedagogy. The work will contribute to the expansion of opportunities for both teachers and students in the process of mastering topics in the subject of pharmacology.